Assessment of Harm Reduction Programs in Behavioral Health Clinics (Triangle) for Covered Veterans - M. Ghiasi; M. Farahbakhsh; A. Hekmatpour (Afarand Scholarly Publishing Institute, 2013)
Introduction: Studies show that veterans exposed to high-risk behavior and drug use are not offset the effects on different aspects of their health and their families, harm reduction programs carried out in health clinics Behavioural (triangle) can maintain and improve health indicators and quality of life of these people. The aim of this study was to assess the impact of harm reduction programs in behavioral health clinics (triangle) on the health and quality of life of veterans. Material and Methods: This study was descriptive analytical with two groups of case and control that was conducted in 2012. For collecting data from demographic questionnaires and standardized tests of "SF-36" was used .To analyze data obtained by the methods of descriptive and analytical statistics were performed. Results: The results showed that the P values of two groups of were physical function scales = 0.001, physical role = 0.128, bodily pain = 0.028, general health =0.046, vitality = 0.042, emotional role = 0.147, social function = 0.001 and mental health = 0.037. Conclusion: Harm reduction programs implemented in behavioral health clinics (triangle) due to improve health dimensions and quality of life that mechanisms can be made larger, thereby reducing the incidence of high risk diseases in veterans and their families.